ANALYSIS OF ROAD TRAFFIC SAFETY IN THE PIŁA POVIAT - Piotr GORZELAŃCZYK; Daria PYSZEWSKA; Tomas KALINA; Martin JURKOVIČ (Scientific Journal of Silesian University of Technology. Series Transport)
Every year, a lot of people lose their lives and health on Polish roads, which at best ends up damaging the car. Resultantly, the high rate of accidents prompted this study in conjunction with the Poviat Police Headquarters in Piła to analyse road traffic safety in the Piła poviat. To this end, road events occurring in Poland and in the Piła poviat were analysed. In addition, the most common types of road incidents were identified alongside the main reasons for their occurrence. By analysing traffic incidents, a map of the most dangerous streets in Piła was created. A survey was conducted to verify the statistical data presented on the state of safety in the Piła poviat. The survey on road safety in the Piła poviat was created in cooperation with the Poviat Police Headquarters in Piła and was conducted among the residents of the Piła poviat. Inhabitants of the Piła poviat feel safe on the roads along the roads of their poviat.